2014
DOI: 10.1021/jp411302d
|View full text |Cite
|
Sign up to set email alerts
|

One-Dimensional Single-Chain Molecular Magnet with a Cross-Linked π–π Coordination Network [{CoII(Δ)CoII(Λ)}(ox)2(phen)2]n

Abstract: A one-dimensional single-chain molecular magnet [{Co II (Δ)Co II (Λ)}(ox) 2 (phen) 2 ] n with a cross-linked π−π coordination network has been synthesized hydrothermally and investigated for its structural and magnetic properties. Oxalate (ox) ligands bridge the paramagnetic Co II metal ions, whereas phenanthroline (phen) ligands exhibit π−π coordination networks. The compound has been thoroughly investigated using room-temperature X-ray and neutron diffraction, infrared spectroscopy, dc magnetization, and rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…The nitronyl nitroxide is a stable spin system which can be linked with the metal center through the O-N groups to produce metal-radical complexes [8][9][10]. Metal-radical complexes which have definite geometry are in favor of the fundamental studies of magneto-structural correlation, especially the way how structural factors affect the metal-organic radical interaction [11][12][13][14]. These investigations are necessary not only for understanding the spin-coupling behaviors between the metal ion and the organic radical but also for the development of new molecular magnetic materials [15,16].…”
Section: (H 2 O) 2 )]mentioning
confidence: 99%
See 1 more Smart Citation
“…The nitronyl nitroxide is a stable spin system which can be linked with the metal center through the O-N groups to produce metal-radical complexes [8][9][10]. Metal-radical complexes which have definite geometry are in favor of the fundamental studies of magneto-structural correlation, especially the way how structural factors affect the metal-organic radical interaction [11][12][13][14]. These investigations are necessary not only for understanding the spin-coupling behaviors between the metal ion and the organic radical but also for the development of new molecular magnetic materials [15,16].…”
Section: (H 2 O) 2 )]mentioning
confidence: 99%
“…A large number of transition metal-radical complexes with various structures and magnetic properties were synthesized and characterized [1,7,9,13,19,20]. A series of zero, one dimensional and multidimensional complexes based on transition metal were reported [6,11,17,18,[21][22][23]. Cobalt (II) complexes have been researched rarely because of large spin-orbital * Corresponding author.…”
Section: (H 2 O) 2 )]mentioning
confidence: 99%
“…The magnetic interaction in the organic magnet is weakened to show a low Curie temperature ( T c ) or even paramagnetism and antiferromagnetism. , In order to improve the ferromagnetic interaction of the organic magnet, intermolecular interaction was introduced into the molecules to enhance the ferromagnetic interaction with a short- or long-range correlation. The molecular magnet with intermolecular interaction forms single chain (1D), 2D network, and 3D-ordered network structures, which result in ferromagnetic ordering, antiferromagnetic ordering, and spin glass states, respectively. Whether the molecular interaction is ferromagnetic or antiferromagnetic is based on the strength and correlation of the intermolecular interaction, which is very important in the design of organic magnets.…”
Section: Introductionmentioning
confidence: 99%
“…There has been an increasing attraction toward the synthesis and characterization of SCMs ,, with new functionalities making such compounds multifunctional as well. , Recent incorporation of π-functional organic molecules in SCMs seems interesting because of the observation of spontaneous magnetization in such compounds, which is a rather rare phenomenon in the series of π-functional magnetic materials. The π–π interaction may give rise to a short-range or a long-range magnetic ordering, and consequently, new materials with distinct magnetic properties may emerge . For example, the oxalate and phenanthroline-based π–π molecular magnet, [{Fe­(Δ)­Fe­(Λ)}­(ox) 2 (phen) 2 ] n exhibits spontaneous magnetization below ∼10 K as reported by Li et al , Further, spontaneous magnetization above room temperature has been observed in a coordination π–π framework of 1D polymeric Cu­(II) chains with 2,2′-bipyridine ligands .…”
Section: Introductionmentioning
confidence: 99%